Efficacy and Safety of Mesenchymal Stem Cells in Treatment of Complex Perianal Fistulas: A Meta-Analysis - Fang Cheng; Zhong Huang; Zhi Li (Stem Cells International)
Complex perianal fistula is a highly debilitating and difficult to treat condition. Local mesenchymal stem cell (MSC) therapy for perianal fistula has shown considerable promise but still remains controversial. Therefore, we performed the meta-analysis to evaluate the efficacy and safety of local MSC therapy for complex perianal fistula. PubMed and Embase databases were searched for published randomized clinical trials (RCTs) that reported local MSC therapy for complex perianal fistulas. The effectiveness and safety data analysis was conducted using RevMan5.3. Subgroup analyses were performed based on the characteristics of the studies. Seven RCTs with 730 participants were included. Local MSC treatment showed significantly higher healing rate (HR) of perianal fistulas compared to control (odds ratio (OR) = 2.03; 95% confidence interval (CI) 1.50, 2.74; P<0.00001). MSCs combined with fibrin glue therapy can improve the HR compared with fibrin glue alone (OR=3.27; 95% CI 1.15, 9.28; P=0.03). Subgroup analyses showed that local therapy can improve the HR in patients with perianal fistulas associated with Crohn’s disease (CD) (OR=2.05; 95% CI 1.41, 3.00; P=0.0002) and cryptoglandular origin (no-Crohn) (OR=2.98; 95% CI 0.86, 10.29; P=0.08). The pooled OR for studies that combined reepithelialization of the external opening with pelvic magnetic resonance imaging (MRI) to evaluate the healing of fistulas was 1.77 (95% CI 1.28, 2.45; P=0.0006). The pooled OR for studies where fistula healing was defined as complete reepithelialization of external openings was 5.92 (95% CI 1.34, 26.15; P=0.02). Both autologous MSCs (OR=3.19; 95% CI 1.05, 9.65; P=0.04) and allogeneic MSCs (OR=1.97; 95% CI 1.34, 2.91; P=0.0006) can obtain higher HR for perianal fistula compared with control. The adipose-derived MSC group can obtain higher HR than the control group (OR=2.29; 95% CI 1.38, 3.79; P=0.001). There were no significant differences in adverse events (AEs) (OR=1.06; 95% CI 0.71, 1.59; P=0.77). None of the adverse events was judged to be related to MSCs. Our study supported that local MSC therapy alone or combined with fibrin glue is safe and efficacious for complex perianal fistula. In the future, more RCTs are needed to confirm this conclusion.